ARCHIVO COMPLEMENTARIO: Producción científica del Instituto Antonio Vidal, Honduras: análisis bibliométrico 1993-2023 - Maradiaga, Edna J.; García, Martha Cecilia; de Kaminsky, Rina Girard; Alger, Jackeline (Revista Médica Hondureña, 2023)